The Incidence of Ocular Tuberculosis in Australia Over the Past 10 Years (2006–2015). (2nd November 2017) - Darian-Smith, Erica; Lin, Ming-Lee; Lim, Lyndell L.; McCluskey, Peter; Hall, Anthony J.
ABSTRACT: Purpose : To determine the incidence and clinical phenotype of ocular tuberculosis in Australia based on the mandatory jurisdictional health notification records for TB. Methods : A whole population retrospective case series (Australia). Patients diagnosed with ocular tuberculosis were identified over the past 10 years (1 January 2006 to 31 December 2015) as recorded by individual Health Department jurisdictions per mandatory health notifications. The incidence rates were calculated based on the available Australian census data. Incidence rates were age and sex standardized. Results : A total of 162 cases of ocular tuberculosis were identified across Australia over a 10-year time period. Of these, 156 participants were overseas born. The 10-year Australian incidence of ocular tuberculosis was 0.77 per 100, 000 people. While there has been a downward trend in overall TB annual incidence rates from 2010 to 2015, over the same period the annual incidence of ocular TB has increased compared to the 4 previous years. Descriptive clinical data regarding the ocular manifestations of TB was available in 73/157 patients. In these 73 patients the commonest manifestations of ocular TB were unspecified uveitis (50.1%), focal, multifocal or serpiginous choroiditis or chorioretinitis (12.3%) and retinal vasculitis (11.0%). Of patients with ocular TB, 4/162 (2.47%) had associated pulmonary TB and 8/162 (4.94%) had associated systemic (non-pulmonary) TB. Systemic anti-TB therapy was administered to 161 patients. Conclusions : The annual Australian incidence of ocular tuberculosis was 0.077 per 100, 000 people. Increasing notifications in the past 6 years may demonstrate increased awareness and changing diagnostic criteria of the disease in the Australian population.